Refactoring OCL annotated UML class diagrams - Marković, Slaviša; Baar, Thomas (Software and systems modeling, 2008)
Refactoring of UML class diagrams is an emerging research topic and heavily inspired by refactoring of program code written in object-oriented implementation languages. Current class diagram refactoring techniques concentrate on the diagrammatic part but neglect OCL constraints that might become syntactically incorrect by changing the underlying class diagram. This paper formalizes the most important refactoring rules for class diagrams and classifies them with respect to their impact on attached OCL constraints. For refactoring rules that have an impact on OCL constraints, we formalize the necessary changes of the attached constraints. Our refactoring rules are specified in a graph-grammar inspired formalism. They have been implemented as QVT transformation rules. We finally discuss for our refactoring rules the problem of syntax preservation and show, by using the KeY-system, how this can be resolved.